2013
DOI: 10.1007/s12013-013-9537-4
|View full text |Cite
|
Sign up to set email alerts
|

Gabaergic Pharmacological Activity of Propofol Related Compounds as Possible Enhancers of General Anesthetics and Interaction with Membranes

Abstract: Phenol compounds, such as propofol and thymol, have been shown to act on the GABAA receptor through interaction with specific sites of this receptor. In addition, considering the high lipophilicity of phenols, it is possible that their pharmacological activity may also be the result of the interaction of phenol molecules with the surrounding lipid molecules, modulating the supramolecular organization of the receptor environment. Thus, in the present study, we study the pharmacological activity of some propofol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 64 publications
(76 reference statements)
3
30
0
Order By: Relevance
“…The two actions of carvacrol were concentration-dependent; EC 50 values for the sEPSC frequency increase and outward current were 0.69 mM and 0.55 mM, respectively. These values were similar to EC 50 value (0.419 mM) for the inhibition of AChE by carvacrol (Jukic et al, 2007) while being somewhat larger than that for carvacrol to inhibit compound action potentials in the frog sciatic nerve (0.34 mM; Kawasaki et al, 2013) [ 3 H]flunitrazepam (a benzodiazepine) binding (i.e., to potentiate GABA A -receptor responses) in cultured mouse cortical neurons (0.235 mM; Reiner et al, 2013). Although the two carvacrol actions in SG neurons had comparable EC 50 values, they appeared to be different in origin, because they occurred in a manner independent of each other in that some neurons produced either outward current (Fig.…”
Section: Discussionsupporting
confidence: 70%
“…The two actions of carvacrol were concentration-dependent; EC 50 values for the sEPSC frequency increase and outward current were 0.69 mM and 0.55 mM, respectively. These values were similar to EC 50 value (0.419 mM) for the inhibition of AChE by carvacrol (Jukic et al, 2007) while being somewhat larger than that for carvacrol to inhibit compound action potentials in the frog sciatic nerve (0.34 mM; Kawasaki et al, 2013) [ 3 H]flunitrazepam (a benzodiazepine) binding (i.e., to potentiate GABA A -receptor responses) in cultured mouse cortical neurons (0.235 mM; Reiner et al, 2013). Although the two carvacrol actions in SG neurons had comparable EC 50 values, they appeared to be different in origin, because they occurred in a manner independent of each other in that some neurons produced either outward current (Fig.…”
Section: Discussionsupporting
confidence: 70%
“…Similarly, carvacrol and chlorothymol have been reported to influence radioligand binding to GABA A Rs in a manner that is consistent with them acting as positive allosteric modulators (Reiner et al, 2013). Carvacrol has also been reported to inhibit the binding of nicotine to nAChRs via a site that is distinct from the orthosteric binding site (Tong et al, 2013).…”
Section: Allosteric Activation Of Human 5-ht 3 Receptorsmentioning
confidence: 80%
“…In addition, both carvacrol and thymol are used as acaricides to control mite (Varroa destructor) infestation of honeybee hives (Damiani et al, 2009). There is evidence that carvacrol and thymol are positive allosteric modulators of both invertebrate and mammalian GABA A Rs (Priestley et al, 2003;García et al, 2006;Reiner et al, 2013). In addition, carvacrol has also been reported to inhibit the binding of nicotine to nAChRs via a site that is distinct from the conventional orthosteric binding site (Tong et al, 2013).…”
mentioning
confidence: 99%
“…In addition, by using Langmuir films and epifluorescence images, we described that all the compounds were able to diffuse into the membrane, placing themselves between phospholipid molecules probably at the head-group region [14]. Finally, by means of fluorescence anisotropy studies we have recently found that all five compounds were able to decrease the microviscosity of artificial membranes [8].…”
Section: Introductionmentioning
confidence: 82%
“…These compounds are GABA-Rs allosteric modulators as they bind to distinct sites to potentiate GABA-evoked currents [1][2][3][4][5]. The phenols propofol and thymol, and lately carvacrol, eugenol and chlorothymol, have been shown to act as positive allosteric modulators on this receptor [6][7][8].…”
Section: Introductionmentioning
confidence: 99%